More than a House of Cards: Developing a Firm Foundation for Streaming Media and Consumer-Licensed Content in the Library - Cross, William (Journal of Copyright in Education & Librarianship, 2016)
This article will introduce traditional library practice for licensing multimedia content and discuss the way that consumer-licensing and streaming services disrupt that practice. Sections II and III describe the statutory copyright regime designed by Congress to facilitate the socially-valuable work done by libraries and the impact of the move from ownership to licensed content. Collecting multimedia materials has always presented special legal challenges for libraries, particularly as licensed content has replaced the traditional practice of purchasing and circulation based on the first sale doctrine. These issues have grown even more complex as streaming services like Netflix and Amazon and video game downloads through services like Steam have come to dominate the landscape. Section IV will describe the way that consumer-licensed materials, which not only remove the ownership that undergirds library practice, but also the ability to negotiate for library use, imperil the congressionally-designed balance. Section V will present a path forward for libraries to develop robust, cutting-edge collections that reflect a sophisticated understanding of the contractual and copyright issues at play.